Kajian Etnobotani dalam Makanan Tradisional Ra’a Rete Khas Bajawa Kecamatan Jerebu’u Kabupaten Ngada - Daud, Maimunah H.; Jimin, Renata Lusitania Bebhe; Nake, Maria Fransiska; Dhone, Maria Tifana; Liko, Viktor Kristian (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Ra'a Rete is a traditional food of the Bajawa people of Ngada Regency, which holds cultural value and potential for development within an ethnobotanical context. This study aims to identify the local plants used in making Ra'a Rete and analyze their role in the Bajawa culinary tradition. The study employed a descriptive qualitative approach, with data collection techniques including field observations and in-depth interviews with community leaders and local culinary practitioners. The results indicate that Ra'a Rete utilizes a variety of local ingredients, such as tubers and spices, which possess high biodiversity and significant nutritional value. Furthermore, this dish plays an important role in preserving the cultural identity of the Bajawa people and provides an opportunity to raise awareness of the sustainable use of local resources. This research is expected to encourage the development of ethnobotanical-based culinary products in Indonesia and preserve traditional cultural heritage.